The Macroeconomic Effects of Overworking in China - Wang, Yi. (Tufts University. Tisch Library., 2021)
Thesis (M.S.)--Tufts University, 2021.; Submitted to the Dept. of Economics.; Advisor: Alan Shapiro.; Committee: Marcelo Bianconi.; Keyword: Labor economics.